EFFECT OF VITAMIN - MINERAL SUPPLEMENTATION IN COMMERCIAL FEED ON THE DIGESTIBILITY COEFFICIENT AND RUMEN FERMENTATION OF BALI CATTLE - Astawa, P.A.; Partama, I.B.G.; Suyadnya, P.; Sutarpa, I.N.S. (Journal of the Indonesian Tropical Animal Agriculture, 2011)
The aim of this study was to find out the influence of vitamin-mineral supplementation ondigestibility and rumen fermentation in Bali cattle. The randomized block design with 4 treatments and 4replications were used in the research. In this study was used 16 Bali cattle with body weight around295.31+23.07 kg. Rations used in the treatments were Treatment A (control): rice straw ad libitum pluscommercial feed; Treatment B: Treatment A ration plus 0.2% vitamin-mineral in commercial feed;Treatment C: Treatment A ration plus 0.3% vitamin-mineral in commercial feed, and Treatment D:Treatment A ration plus 0.4% vitamin-mineral in commercial feed. Parameters measured were nutrientdigestibility, rumen metabolites and urinary allantoin. The results showed that supplementation ofvitamin-mineral at 0.2 - 0.4% in commercial feed did not increase the digestibility of dry matter, organicmatter, crude protein and crude fiber, except for dry matter and organic matter digestibilities at 0.2%supplementation (p<0.05). However, the vitamin-mineral supplementation increased concentrations ofpartial VFA and ammonia as well as for methane gas production, except for VFA and ammonia at 0.4%level. Vitamin-mineral supplementation at 0.2-0.4% level did not affected pH value of rumen fluid andurinary allantoin.